From Diagnosis to Treatment: The Collaborative Efforts of Laboratory, Nursing, Medical Devices, Pharmacy Technician in Patient Management - Haitham Abdullah Fares Abanami1 Ahmed Saeed Hazzazy2 Abdulaziz Saad Al-Mutairi3 Abdullah Marzouq M Alsolami4 Khalid Omar Noory Alsayed5 Bader Saeed Mushaylih ALmutairi6 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The context of healthcare delivery and responsibility is undergoing transformation. The concept of patient-centered care is increasingly becoming recognized worldwide, as patients assume a bigger role in managing their own health and participate in the decision-making process for diagnosing and treating illnesses. The fields of laboratory nursing, medical devices, and pharmacy should actively adopt this transformation and engage in a collaborative relationship with patients and physicians who use clinical services. Enhanced communication is essential for fostering involvement, which involves providing educational information and assistance. Knowledge management should be tailored to address the specific needs and interests of each stakeholder group.